PENGARUH BUDGETARY GOAL CHARACTERISTICS, KOMPENSASI TERHADAP KINERJA APARAT PEMDA DENGAN MOTIVASI SEBAGAI VARIABEL MODERASI (Studi Kasus pada Dinas-Dinas Kabupaten Rokan Hilir) - Tengku Ramona Fitri; Emrinaldi Nur DP; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
Performance is achievement implementation representation of an action/program/policy in order to achieved objectives, goals, mission and vision of the organization. This study aimed at re-examining the effect of budgetary goal characteristics, compensation to the performance of local government officials and also to examine whether motivation could act as moderating variables in the public sector organizations. This study uses a purposive sampling method with 72 respondent in different departments. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 17 for windows. The results indicated that budgetary goal characteristics and compensation has a positive and significant effect on the performance of local government officials. The study also resulted that motivation can not to moderate the relationship between budgetary goal characteristics to the performance of local government officials, while motivation is able to moderate the relationship between compensation to the performance of local government officials performances in Rokan Hilir district.Keywords: budgetary goal characteristics, compensation, performance, motivation and moderation.